A call for action: Insights from the pre‐COP28 scholarly discourse and beyond the operationalization of the Loss and Damage Fund - Dorcas Stella Shumba (Climate Resilience and Sustainability)
Abstract This paper conducts a semisystematic literature review from 2021 to 2023, focusing on loss and damage (L&D). Drawing upon the works of various scholars, it synthesizes critical concerns raised in the literature and assesses whether these concerns were addressed by the Transitional Committee's report on the operationalization of the new funding arrangements for responding to loss and damage, as outlined in COP 28 decisions 1/CP.28 and 5/CMA.5. By analyzing scholarly discussions on L&D leading up to COP 28, the study gauges the extent to which academic concerns have been addressed and identifies areas requiring improvement for better management of climate change‐induced L&D effects. The findings provide valuable insights for ongoing deliberations on the Loss and Damage Fund (LDF), offering guidance for policymakers as they address these challenges. Additionally, the paper informs future policy directions to ensure responsiveness to the needs of communities affected by climate change‐induced L&D. Lastly, the study contributes to ongoing scholarly dialogues by laying the groundwork for future research endeavors in this critical area.